Pengembangan Website Penjualan Alat Terapi (Studi Kasus: Klinik Physiostore Tulungagung) - Norma Desitasari; Buce Trias Hanggara; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Physiostore clinic is a therapy clinic offering therapy services and selling several therapy products. From the beginning, this clinic does not store sales data where every transaction to be recorded manually and ordering products only by phone and there was no recording of patient data coming in for therapy. From these problems, a web-based system that can make it easier for the manager to store patient data and product sales data was created. But also, customers can easily place an order on the website. This website was developed using the laravel framework, the programming language PHP, MySQL, CSS, and javascript. The system development stage starts from the requirement analysis through interviews with the owner of Physiostore where the results of the requirement analysis are illustrated by the use case diagram, use case scenario, and activity diagram. The system design is illustrated by the sequence diagram, class diagram, and physical data model. The website implementation used shipping charges and chatting API. Validation testing of the system gets a percentage 100% valid results where the system complies with the requirements specifications and usability testing was done using the system usability testing (SUS) get an average value 82 where the system categorized on Good with B on value scale and the acceptability range is on acceptable category.